(untitled) (Raparin Journal of Humanities (RJH), 2023)
Harassment is a global phenomenon these days, and it’s an issue facing communities around the globe. This has attracted researchers to write and comment on the phenomenon. The problem is a global threat, in particular to females. Although men also face harassment, but this is not the focus of this paper. Among females, the generation who are in particular targeted are adolescent girls. The main purpose of this paper is to find the correlation between harassment and mental well-being of adolescent girls. Researchers have made use of the descriptive-analytic method. For this purpose, researchers have prepared a form which includes the standards of harassment. The form has two main parts. The standards of harassment has 32 points, and the standards of mental health has 22 points. Samples were taken randomly from (334) adolescent girls from high school levels in Rania city. Researchers have utilized both SPSS and AMOS programs. This paper has found that none of the forms of (harassment, physical, verbal, symbolic and online), have become a common phenomenon among the samples taken. Instead, the problem appears in the form of instances. It is also found that the mental health of the participants is in good standing. However, participants who have faced harassment at ages 6 to 10 appear to have weaker mental health than other ages. Data also shows that adolescences who face harassment suffer from more mental health problems than their peers who have not faced the problem. In addition, adolescent girls who have faced online harassment have weaker mental health compared to their peers who have faced other forms of harassment.